Gating of trigemino-facial reflex from low-threshold trigeminal and extratrigeminal cutaneous fibres in humans. Issue 9 (September 1992) - Rossi, A; Scarpini, C
Abstract : Changes in the size of the test components (R1 and R2) of the trigemino-facial reflex were studied after electrical subliminal conditioning stimulation were applied to the trigeminal, median and sural nerves. After conditioning activation of the trigeminal nerve (below the reflex threshold), the early R1 reflex component showed phasic facilitation, peaking at about 50 ms of interstimulus delay, followed by a long-lasting inhibition recovering at 300-400 ms. The same conditioning stimulation resulted in a monotonic inhibition of the late R2, starting at 15-20 ms, with a maximum at 100-150 ms and lasting 300-400 ms. Intensity threshold for both the R1 and R2 changes ranged from 0.90 to 0.95 times the perception threshold. A similar longlasting inhibition of the R2 reflex response was also seen after conditioning stimulation applied to low-threshold cutaneous afferents of the median and sural nerves. The minimum effective conditioning-test interval was 25-30 ms and 40-45 ms respectively and lasted 600-700 ms. By contrast the early R1 reflex response exhibited a slight long-lasting facilitation with a time course similar to that of the R2 inhibition. The threshold intensity to obtain facilitation of the R1 and inhibition of the R2 test responses after conditioning volley in the median and sural nerves was similar and ranged from 0.9 to 1.2 times the perception threshold. These results demonstrate that low-threshold cutaneous afferents from trigeminal and limb nerves exert powerful control on trigeminal reflex pathways, probably via a common neural substrate. There is evidence that, in addition to any post-synaptic mechanism which might be operating, presynaptic control is a primary factor contributing to these changes.